Detection of Chlamydiaceae and Chlamydia-like organisms on the ocular surface of children and adults from a trachoma-endemic region - Ehsan Ghasemian (Nature Portfolio, 2018)
Abstract Trachoma, the leading infectious cause of blindness, is caused by Chlamydia trachomatis (Ct), a bacterium of the phylum Chlamydiae. Recent investigations revealed the existence of additional families within the phylum Chlamydiae, also termed Chlamydia-like organisms (CLOs). In this study, the frequency of Ct and CLOs was examined in the eyes of healthy Sudanese (control) participants and those with trachoma (case). We tested 96 children (54 cases and 42 controls) and 93 adults (51 cases and 42 controls) using broad-range Chlamydiae and Ct-specific (omcB) real-time PCR. Samples positive by broad-range Chlamydiae testing were subjected to DNA sequencing. Overall Chlamydiae prevalence was 36%. Sequences corresponded to unclassified and classified Chlamydiae. Ct infection rate was significantly higher in children (31.5%) compared to adults (0%) with trachoma (p < 0.0001). In general, 21.5% of adults and 4.2% of children tested positive for CLOs (p = 0.0003). Our findings are consistent with previous investigations describing the central role of Ct in trachoma among children. This is the first study examining human eyes for the presence of CLOs. We found an age-dependent distribution of CLO DNA in human eyes with significantly higher positivity in adults. Further studies are needed to understand the impact of CLOs in trachoma pathogenicity and/or protection.